Asymmetric Catalytic Formal 1, 4‐Allylation of β, γ‐Unsaturated α‐Ketoesters: Allylboration/Oxy‐Cope Rearrangement. Issue 34 (12th July 2019) - Tang, Qiong; Fu, Kai; Ruan, Peiran; Dong, Shunxi; Su, Zhishan; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly enantioselective formal conjugate allyl addition of allylboronic acids to β, γ‐unsaturated α‐ketoesters has been realized by employing a chiral Ni II / N, N ′‐dioxide complex as the catalyst. This transformation proceeds by an allylboration/oxy‐Cope rearrangement sequence, providing a facile and rapid route to γ‐allyl‐α‐ketoesters with moderate to good yields (65–92 %) and excellent ee values (90–99 % ee ). The isolation of 1, 2‐allylboration products provided insight into the mechanism of the subsequent oxy‐Cope rearrangement reaction: substrate‐induced chiral transfer and a chiral Lewis acid accelerated process. Based on the experimental investigations and DFT calculations, a rare boatlike transition‐state model is proposed as the origin of high chirality transfer during the oxy‐Cope rearrangement. Abstract : A highly efficient catalytic asymmetric allylboration/oxy‐Cope rearrangement reaction sequence of β, γ‐unsaturated α‐ketoesters with allylboronic acids has been realized by employing a Ni II / N, N ′‐dioxide complex as the catalyst. This transformation provides a facile and rapid route to formal allyl conjugate addition products, chiral γ‐allyl‐α‐ketoesters, with good results.